Biodegradation of the pyrethroid cypermethrin by bacterial consortia collected from orange crops - Birolli, Willian Garcia (2022)
Pyrethroids, such as cypermethrin (CYP), are widely employed in agriculture, promoting environmental pollution and the need for efficient decontamination methods. In this study, bacteria from orange crops were explored for CYP biodegradation. Among 40 tested bacterial strains, 20 grew in the presence of CYP and 19 performed statistically significant CYP biodegradation in 5 days (20.5%–97.8%). In addition, 3-phenoxybenzoic acid, the main metabolite from CYP, was quantified ranging from 1.1 mg.L−1 to 32.1 mg.L−1. The five most efficient strains, and consortia composed of 5, 10 and 20 bacteria biodegraded the CYP formulation as sole carbon source in phosphate buffer and in minimum mineral medium. Under optimized conditions determined employing Response Surface Methodology, Bacillus sp. CSA-1 and the consortium composed of 10 strains biodegraded 71.0% and 71.6% CYP in 24 h, respectively. Moreover, metabolite identification enabled the proposal of an extended biodegradation pathway with 29 identified compounds, including different new amide and amine derivatives that expanded the knowledge about the fate of this compound in the environment. Experiments of bioaugmentation in soil using Bacillus sp. CSA-1 and the consortium of 10 bacterial strains resulted in faster CYP biodegradation than natural attenuation, showing that the selection of efficient strains for composing a consortium is an interesting approach for bioremediation of pyrethroids.